Social life cycle assessment in solar dryer house for postharvest loss management technology: Application of UNEP / SETAC in Tanzania - Sungau, Joseph; Mkuna, Eliaza; Abeid, Ashiraf; Lyakurwa, Felichesmi; Manouchehr, Shokri (Arabian Journal of Business and Management Review (Kuwait Chapter), 2024)
Nil